Intertwined Sovereign and Bank Solvencies in a Model of Self-Fulfilling Crisis - Adler, Gustavo (Washington, D.C. : International Monetary Fund, 2012)
Large fiscal financing needs, both in advanced and emerging market economies, have often been met by borrowing heavily from domestic banks. As public debt approached sustainability limits in a number of countries, however, high bank exposure to sovereign risk created a fragile inter-dependence between fiscal and bank solvency. This paper presents a simple model of twin (sovereign and banking) crisis that stresses how this interdependence creates conditions conducive to a self-fulfilling crisis.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet